Towards a more comprehensive approach for a total economic assessment of vaccines?: 1. The building blocks for a health economic assessment of vaccination. Issue 1 (1st January 2017) - Standaert, Baudouin; Rappuoli, Rino
ABSTRACT: ​Since we were born, we all take preventative actions to avoid unpredictable adverse conditions. Some actions are done automatically. Others require a conscious choice, either for personal or social benefit. A distinction can therefore be drawn between non-active and active prevention, and between individual and social prevention. Active prevention requires making a choice in time, effort, and cost. We call it an economic choice. Vaccines belong to the group of active and social prevention. Because a vaccination program is an economic social choice, how should it be valued, and what cost should we pay for? To date, the economic evaluations developed for treatment have been applied to vaccines. However, over 25 different characteristics differentiate vaccines from treatment. For example, the benefit of vaccination is measured at the population level not at the individual level, the main effect of prevention is societal and not an individual-based gain only, and the biggest hurdle to implement a new vaccine is the initial budget investment and not so much its estimated 'value for money'. This makes the current application of incremental cost-utility analysis difficult for vaccines for a comprehensive evaluation. New approaches may be needed to capture the full economic benefit of vaccines.​